Comparison of interleukin-1β levels in gingival crevicular fluid and peri-implant crevicular fluid and its relationship with clinical indexes. - Siamak Yaghobee; Afshin Khorsand; Mojgan Paknejad (Frontiers in Dentistry, 2013)
Interleukin-1β (IL-1β) is one of the most important cytokines which seems to have an important role in the inflammatory process in gingival and peri-implant tissues. The aim of this split-mouth study was to investigate the relationship between the concentration of IL-1β in gingival crevicular fluid (GCF) and peri-implant crevicular fluid (PICF) and clinical parameters such as plaque index (PI), gingival index (GI), pocket depth (PD) and bone loss (BL).In 32 patients, PICF and GCF samples of 41 implants and 41 contralateral teeth were collected and IL-1β was determined by enzyme-linked immunosorbent assay (ELISA). PI,GI,PD and BL were recorded for each of the samples.The positive correlation between the level of IL-1β and PI, GI, PD and BL in both groups was observed (P